Pengembangan Instrumen Dokumentasi Catatan Potensi Siswa Berdasarkan Manajemen Risiko dalam ISO 9001:2015 - Arie Purwanto; Palasara Brahmani Laras (Universitas Mathla'ul Anwar Banten, 2020)
DEVELOPMENT OF INSTRUMENTATION DOCUMENTATION OF POTENTIAL STUDENTS BASED ON RISK MANAGEMENT IN ISO 9001: 2015. This dedication is based on the devotion in the documentation of students' potential risks. The purpose of this service is to help teachers, especially guidance and counseling teachers, be able to measure and document the potential risks experienced by their students. In addition, this instrumen was deliberately developed so that it is expected to be able to make a positive contribution to the teacher in designing classroom learning. By using this instrumen teachers are expected to also be able to choose and use learning models that are in accordance with the results of the analysis that has been done. From the service that has been done, it is obtained that 92% of teachers strongly agree with the holding of this service activity. Further analysis shows that there is a real difference in understanding between before and after with a p-value of 0.00 with a correlation between the differences of 0.816. It can be said that assistance is effective in answering partner problems.